2013
DOI: 10.1149/05002.1959ecst
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-TiO2 Composite Nanofibers as a Promising Support for PtRu Anode Catalyst of DMFC

Abstract: Carbon-TiO2 composite nanofibers, (C-TiO2) NF, have been fabricated by electrospinning and used as a support for PtRu nanoparticles for the catalyst of methanol oxidation. The catalytic activity and durability of the prepared catalyst was compared with that supported on carbon black, Vulcan XC-72R, and TiO2 nanoparticles. The crystal structure and electrocatalytic properties of the as-obtained catalysts have been investigated by X-ray diffraction, cyclic voltammetry and chronoamperometry. The PtRu prepared on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Various research groups have demonstrated the incorporation of some of the metal oxides (TiO 2 , IrO 2 , CeO 2 , V 2 O 5 , WO x , MoO 3, NiTiO 3 ) as active support material in the anode electrocatalysts for the improvement of the MOR activity in the DMFCs [30][31][32][33][34][35][36][37]. In this aspect, TiO 2 has been recognized as one of the promising MOR reaction promoters with high stability under acidic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Various research groups have demonstrated the incorporation of some of the metal oxides (TiO 2 , IrO 2 , CeO 2 , V 2 O 5 , WO x , MoO 3, NiTiO 3 ) as active support material in the anode electrocatalysts for the improvement of the MOR activity in the DMFCs [30][31][32][33][34][35][36][37]. In this aspect, TiO 2 has been recognized as one of the promising MOR reaction promoters with high stability under acidic environment.…”
Section: Introductionmentioning
confidence: 99%
“…An enhancement in the CO tolerance of the Pt electrocatalysts for the aforementioned applications would result in the following: (a) the low-temperature fuel cell systems would not require ultrapure hydrogen, and the process of hydrogen purification will become more efficient thereby reducing the existing costs significantly; (b) higher concentration of methanol or ethanol can be used in alcohol-based fuel cells allowing higher current and output power along with enhanced durability; (c) hydrogenation of hydrocarbon would become more effective and economical; and most importantly, (d) increased efficiency of Pt catalyst would mean reduced dependence on this rare and limited resource. Currently, the most effective way of increasing CO tolerance is the use of oxophilic elements such as Ru, Pd, Au, and so forth, to form alloys with Pt. However, this is an extremely costly solution as all these elements (like Pt) are in limited supply and hence quite expensive. It is, therefore, essential to investigate other cheaper alternatives such as surface modification and functionalization of the underlying support to provide synergistic effects for enhancing the CO-tolerance of Pt.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study has been conducted on Pd loaded on carbonized TiO 2 nanotubes for alcohol electrooxidation [23]. Furthermore, there have been other studies that use TiO 2 on carbon fibers [24,25], nanotubes [26][27][28], and nanoparticles [29] for electrocatalysts. To the best of our knowledge, carbonized anatase TiO 2 nanobelts have not yet been researched as a support for Pd catalysts for electrooxidation.…”
Section: Introductionmentioning
confidence: 90%